Effectiveness of An Educational Program on Caregivers’ knowledge about Nutritional Status of Children with Leukemia at Hematology Center in Medical City - Mushtaq Najmuldeen Ali, Eqbal Ghanian Ali Ma’ala (Pakistan Journal of Medical & Health Sciences, 2022)
Background: One of the disorders for which cancer research and therapy are expected to bring positive results is a childhood acute leukemia1. Childhood cancer is a prominent cause of child mortality in affluent nations and a well-known contributor to malnutrition and death in underdeveloped countries, particularly those with poor socioeconomic level2. Objectives: The study aims to assess caregivers’ knowledge about nutritional status of children with leukemia and construct educational program according to the assessment needs of caregivers about nutritional status Research Methodology: Quantitative research “quasi-Experimental Study one group” carried out from the period of 9th of February 2021 to the 20th April of 2022. The validity of the instruments was achieved through a panel of (10) experts. The questionnaire is composed of two parts, each of which is divided into many sections. The first part deals with demographic information about caregivers, while the second part is separated into two categories, (first section contain 14 multiple choice questions and second section contain 6 true and falls question). The data in this study were analyzed using the Statistical Package for Social Science (SPSS) version 26 Results: The current study’s findings indicated that the group of (25) caregivers participants’ age group between (25-34) years represents (50%) and the mothers level of educational in the results of the presents study displayed that the percentage of those with university education accounts (1/4) of the total study sample and their number represents was (7) mothers. The family socio-economic status level in the result of the present study indicate that half of samples come from the middle levels. The present study result reveals the caregiver’s age with their knowledge pass the first section of the question and represent (15.4%) of the sample study, while the second section of the knowledge question represent (23.1) of sample study at age (25-34)years. Recommendation: Education program for caregiver’s with child leukemia to improve their knowledge and attitudes. Working on the establishment of compulsory courses for caregiver’s who have children with leukemia in collaboration with the Ministry of Health and the centers of treating the child with cancer. Encouraging caregiver’s to learn about nutrition statues, if not financially at least let it be morally.